Utvärdering av produktionsledarens användning av Holmen Skogs datorbaserade stödsystem vid operativ planering av avverkning - Erixon, Nils (2011)
The forestry companies’ operational planning process is these days dependent on reliable, efficient and user-friendly computer-based support systems. This study is an evaluation of Holmen Skog's current computer-based systems.